Qualea grandiflora, a Brazilian Cerrado medicinal plant presents an important antiulcer activity - Hiruma-Lima, C. A.; Santos, Lourdes Campaner dos [UNESP]; Kushima, H.; Pellizzon, C. H.; Silveira, G. G.; Vasconcelos, PCP; Vilegas, Wagner [UNESP]; Brito, ARMS (Elsevier B.V., 2006)
Qualea grandiflora is one of the species widely used in folk medicine to treat gastric ulcers in Cerrado of the central region of Brazil. The hydroalcoholic extract of bark (HE) of Qualea grandiflora was investigated for their ability to prevent and heal lesions in the gastric mucosa. The oral administration of HE exhibited antiulcer activity decreasing the ulcerative index induced by HCl/ethanol solution, indomethacin/bethanechol and stress. In the Shay model, results showed that HE (p.o.) only reduced the severity of gastric lesions without effects on pH, gastric acidity or volume. When given by intraduodenal route, HE changed the pH, but did not modify the other parameters of the gastric juice. These data were in accordance with those obtained when HE was administered orally for 14 days after gastric ulcers were induced by acetic acid in rats. HE presented healing process in subacute gastric ulcer induced by acetic acid in rats. Moreover, histological examinations showed the simple columnar epithelium, lamina propria with simple branched tubular glandules with dilated lumen and large amounts of mucus secretion. Phytochemical investigation of HE led to the detection of terpenes, steroids, saponins, phenolic compounds and tannins in this extract, which may be involved in the observed activity. (c) 2005 Elsevier B.V.. All rights reserved.
Keywords: Qualea grandiflora; vochysiaceae; antiulcer effect; healing activity; medicinal plants; Cerrado